Treatment of patients with relapsed or refractory CD19+ lymphoid disease with T lymphocytes transduced by RV-SFG.CD19.CD28.4-1BBzeta retroviral vector: a unicentre phase I/II clinical trial protocol - Schubert, Maria-Luisa; Schmitt, Anita; Sellner, Leopold; Neuber, Brigitte; Kunz, Joachim; Wuchter, Patrick; Kunz, Alexander; Gern, Ulrike; Michels, Birgit; Hofmann, Susanne; Hückelhoven-Krauss, Angela; Kulozik, Andreas; et al. (BMJ open, 2019)
Introduction Chimeric antigen receptor (CAR) T cells spark hope for patients with CD19+ B cell neoplasia, including relapsed or refractory (r/r) acute lymphoblastic leukaemia (ALL) or r/r non-Hodgkin’s lymphoma (NHL). Published studies have mostly used second-generation CARs with 4-1BB or CD28 as costimulatory domains. Preclinical results of third-generation CARs incorporating both elements have shown superiority concerning longevity and proliferation. The University Hospital of Heidelberg is the first institution to run an investigator-initiated trial (IIT) CAR T cell trial (Heidelberg Chimeric Antigen Receptor T cell Trial number 1 [HD-CAR-1]) in Germany with third-generation CD19-directed CAR T cells. - Methods and analysis Adult patients with r/r ALL (stratum I), r/r NHL including chronic lymphocytic leukaemia, diffuse large B-cell lymphoma, follicular lymphoma or mantle cell lymphoma (stratum II) as well as paediatric patients with r/r ALL (stratum III) will be treated with autologous T-lymphocytes transduced by third-generation RV-SFG.CD19.CD28.4-1BB zeta retroviral vector (CD19.CAR T cells). The main purpose of this study is to evaluate safety and feasibility of escalating CD19.CAR T cell doses (1-20×106 transduced cells/m2) after lymphodepletion with fludarabine (flu) and cyclophosphamide (cyc). Patients will be monitored for cytokine release syndrome (CRS), neurotoxicity, i.e. CAR-T-cell-related encephalopathy syndrome (CRES) and/or other toxicities (primary objectives). Secondary objectives include evaluation of in vivo function and survival of CD19.CAR T cells and assessment of CD19.CAR T cell antitumour efficacy.HD-CAR-1 as a prospective, monocentric trial aims to make CAR T cell therapy accessible to patients in Europe. Currently, HD-CAR-1 is the first and only CAR T cell IIT in Germany. A third-generation Good Manufacturing Practice (GMP) grade retroviral vector, a broad spectrum of NHL, treatment of paediatric and adult ALL patients and inclusion of patients even after allogeneic stem cell transplantation (alloSCT) make this trial unique. - Ethics and dissemination Ethical approval and approvals from the local and federal competent authorities were granted. Trial results will be reported via peer-reviewed journals and presented at conferences and scientific meetings. - Trial registration number Eudra CT 2016-004808-60; NCT03676504; Pre-results.